2015
DOI: 10.1159/000381832
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Female Sex on Stroke Risk Factors, Care, Outcome and Rehabilitation: An Asian Perspective

Abstract: Background: Stroke affects 16.9 million people annually and the greatest burden of stroke is in low- and middle-income countries, where 69% of all strokes occur. Stroke risk factors, mortality and outcomes differ in developing countries as compared to the developed world. We performed a literature review of 28 articles pertaining to epidemiology of stroke in Asian women, stroke risk factors, gender-related differences, and stroke outcomes. Summary: Asian women differ from women worldwide due to differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 63 publications
2
27
1
1
Order By: Relevance
“…The use of oral contraceptives and dependence on tobacco or alcohol, which are well-known risk factors of ischemic stroke, are less prevalent in Asian women than in women in other parts of the world. 34 Last, we cannot exclude the possibility that women have a low stroke awareness and have poorer access to medical care. The present finding, that women have a similar risk of stroke as do men when stratified according to risk factors, needs to be validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The use of oral contraceptives and dependence on tobacco or alcohol, which are well-known risk factors of ischemic stroke, are less prevalent in Asian women than in women in other parts of the world. 34 Last, we cannot exclude the possibility that women have a low stroke awareness and have poorer access to medical care. The present finding, that women have a similar risk of stroke as do men when stratified according to risk factors, needs to be validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several unique risk factors have been reported for the occurrence of stroke in women [1,2] . Women tend to survive longer and experience stroke at an older age, and this fact suggests an increase in the incidence of stroke in women due to the aging of the population [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these studies, in the present study, we found that women were more likely than men to have POCI, severe stroke, hypertension, and obesity but less likely to be current smokers and to consume alcohol. The delayed time to hospital admission in women could explain the greater frequency of severe stroke [30]. …”
Section: Discussionmentioning
confidence: 99%